An Overview of the European Tax Havens - Loredana Maftei (CES Working Papers, 2013)
In the actual context of economic globalization, tax havens represent a significant obstacle for global governments seeking to increase their fiscal incomes and a source of polarization of income and wealth. Statistics reports showed that tax havens hold at least 10 trillion in assets, money generally controlled and hidden by major players from the political and financial areas, as well as from criminal ones. The paper introduces the present situation of European tax havens, with the major poles of action. The conclusion finds the real efforts of international bodies such as OECD, to interdict opportunities to avoid taxation.
Keywords: H25; H26; H87; F21; 330; tax haven; offshore financial centres; globalization; illegal markets Romania